Accelerating Business Law Dynamization through Proposed Amendments to Indonesian Consumer Protection Law - Norma Sari (Universitas Ahmad Dahlan, 2023)
Introduction to The Problem: The Consumer Protection Law No. 8 of 1999 which was enacted in 2000 has been in force for over 20 years. The current circumstance in the realm of business law requires more progressive regulations on digital business activities, more efficient dispute resolution, and effective consumer protection due to the rapid technological developments. Hence, the need of an amendment to the current consumer protection law must be examined thoroughly and analyzed deeply.Purpose/Objective Study: This research aims to examine and to present the arguments on several issues in relating to the urgency of amending the Consumer Protection Law No. 8 of 1999 in order to accelerate the dynamization of business law.Design/Methodology/Approach: This is a doctrinal legal research that uses a qualitative approach. In this research, the authors utilized secondary data sourced from literature study on the primary, secondary, and tertiary legal materials. The authors analyzed the data by using Systematic Content Analysis which is frequently used by social scientists to analyze the inteview tranrscripts, literatures, and field notes, among other sources.Findings: The results indicate that there are six noteworthy points regarding the extent of the business entity, standard clauses, data protection, and some issues on a dispute settlement institution. These are sufficient to support in proposing an amendment to the recent Consumer Protection Law.Paper Type: Research Article